The diagnostic value of gastroesophageal reflux disease (GERD) symptoms and detection of pepsin and bile acids in bronchoalveolar lavage fluid and exhaled breath condensate for identifying lung transplantation patients with GERD-induced aspiration - Reder, Nicholas P. (Surg Endosc, 2014)
BACKGROUND: Gastroesophageal reflux disease (GERD) is thought to lead to aspiration and bronchiolitis obliterans syndrome after lung transplantation. Unfortunately, the identification of patients with GERD who aspirate still lacks clear diagnostic indicators. The authors hypothesized that symptoms of GERD and detection of pepsin and bile acids in the bronchoalveolar lavage fluid (BAL) and exhaled breath condensate (EBC) are effective for identifying lung transplantation patients with GERD-induced aspiration. METHODS: From November 2009 to November 2010, 85 lung transplantation patients undergoing surveillance bronchoscopy were prospectively enrolled. For these patients, self-reported symptoms of GERD were correlated with levels of pepsin and bile acids in BAL and EBC and with GERD status assessed by 24-h pH monitoring. The sensitivity and specificity of pepsin and bile acids in BAL and EBC also were compared with the presence of GERD in 24-h pH monitoring. RESULTS: The typical symptoms of GERD (heartburn and regurgitation) had modest sensitivity and specificity for detecting GERD and aspiration. The atypical symptoms of GERD (aspiration and bronchitis) showed better identification of aspiration as measured by detection of pepsin and bile acids in BAL. The sensitivity and specificity of pepsin in BAL compared with GERD by 24-h pH monitoring were respectively 60 and 45 %, whereas the sensitivity and specificity of bile acids in BAL were 67 and 80 %. CONCLUSIONS: These data indicate that the measurement of pepsin and bile acids in BAL can provide additional data for identifying lung transplantation patients at risk for GERD-induced aspiration compared with symptoms or 24-h pH monitoring alone. These results support a diagnostic role for detecting markers of aspiration in BAL, but this must be validated in larger studies.